2006
DOI: 10.1152/ajpheart.01179.2005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary flaxseed on vascular contractile function and atherosclerosis during prolonged hypercholesterolemia in rabbits

Abstract: -Dietary flaxseed has significant anti-atherogenic effects. However, the limits of this action and its effects on vascular contractile function are not known. We evaluated the effects of flaxseed supplementation on atherosclerosis and vascular function under prolonged hypercholesterolemic conditions in New Zealand White rabbits assigned to one of four groups for 6, 8, or 16 wk of feeding: regular diet (RG), 10% flaxseed-supplemented diet (FX), 0.5% cholesterol-supplemented diet (CH), and 0.5% cholesterol-and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
73
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 80 publications
(80 reference statements)
2
73
2
1
Order By: Relevance
“…Plasma fatty acids were measured by gas chromatography as described in detail elsewhere (Dupasquier et al, 2006(Dupasquier et al, , 2007. Briefly, blood samples were centrifuged at 1800  g for 5 min at 4 1C to obtain plasma, and then the plasma fatty acids were derived and then analyzed using a Varian CP-3800 gas chromatograph (Varian Inc., Palo Alto, CA, USA), equipped with a flame ionization detector and Varian CP-Sil 88 capillary column (Varian; 60 m  0.25 mm  0.20 mm).…”
Section: Study Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Plasma fatty acids were measured by gas chromatography as described in detail elsewhere (Dupasquier et al, 2006(Dupasquier et al, , 2007. Briefly, blood samples were centrifuged at 1800  g for 5 min at 4 1C to obtain plasma, and then the plasma fatty acids were derived and then analyzed using a Varian CP-3800 gas chromatograph (Varian Inc., Palo Alto, CA, USA), equipped with a flame ionization detector and Varian CP-Sil 88 capillary column (Varian; 60 m  0.25 mm  0.20 mm).…”
Section: Study Proceduresmentioning
confidence: 99%
“…C17:0 was used as the internal standard and the fatty acid contents of the sample were identified by comparison with an authentic standard, GLC-462 (Nu-Chek Prep, Elysian, MN, USA). Plasma cholesterol and triglyceride (TG) levels were measured as described (Dupasquier et al, 2006(Dupasquier et al, , 2007.…”
Section: Study Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike drug therapy, n-3 PUFAs have fewer and milder side effects and are generally considered safe (37). Moreover, milled flaxseed has proven to be cardioprotective and antiatherogenic in animal models (7,22,23,44) as well as in clinical settings (50). However, although flaxseed can diminish the progression of atherosclerotic plaques, it is unclear if dietary supplementation with flaxseed can regress established atherosclerotic plaques.…”
mentioning
confidence: 99%
“…Although the biological effects of ALA may not be the same as those for EPA and DHA, we have recently demonstrated that flaxseed products exhibit antiatherosclerotic activities in cholesterol-fed rabbits and LDL-receptor knockout (KO) mice (10,11). The mechanisms underlying these beneficial properties of flaxseed may be mediated through its beneficial effects on lipid metabolism, platelet function, inflammation, endothelial cell function, and arrhythmia (36).…”
mentioning
confidence: 99%